Social Well-Being at School: Development and Validation of a Scale for Primary Education Students - Moliner, Lidon; Alegre, Francisco; Cabedo-Mas, Alberto; Chiva-Bartoll, Oscar (Frontiers in Education, 2021)
This study presents the development and validation of a scale for Primary Education students that measures social well-being. A seven-factor structure was defined, with the factors being: achievement, cooperation, cohesion, coexistence, attitude towards school, attitude towards diversity and solidarity. 14 experts from independent European universities participated in the validation process of the scale. The 38-item scale showed considerable reliability (Cronbach’s alpha =.91). The confirmatory factor analysis confirmed the original seven-factor structure with consistent goodness and badness of fit indexes. The promising results in this study suggest that this scale may be suitable for an international audience.